The Indonesia Government's Strategy in Arrest and Confiscation of Criminal Corruption (Corruptor) Assets Abroad - Mohas, Muhyi Mohas; Mega Jaya, Belardo Prasetya; Fasyehhudin, Mohamad; Mega Jaya, Arizon (Faculty of Law, Universitas Jenderal Soedirman, 2021)
Eradication efforts of corrupting in Indonesia have been carried out, but until now there are still many corruption cases that have not been resolved in various ways by the perpetrators or corruptors. Corruptors often drain the funds from the results of corrupting, even the corruptors then go or run abroad. This raises problems in the process of law enforcement and recovery of financial and economic losses in the country, namely the mechanism for returning assets resulting from criminal acts of corrupting abroad. Therefore, the objectives of this study are to (1) Explain how is Indonesia Government's strategy in arrest and confiscation of criminal corruption (corruptor) assets abroad. (2) Explain how is international treaties concerning the seizure of assets resulting from criminal acts of corrupting are abroad. The research method used in this research is qualitative with a juridical legal approach normative. The results showed that the cooperation between countries is the best strategy that can be done by the Indonesia government in overcoming problems of sovereignty. Some examples of these forms of international cooperation are extradition treaties (extradition), Mutual legal assistance in criminal matters (MLA). The mechanism for the return of assets in MLA consists of four stages of the asset return process (Article 46 Chapter IV, UNCAC).Keywords: international cooperation; eradication of corruption; confiscation of assets; extradition; mutual legal assistance in criminal matters.